2021
DOI: 10.21037/tlcr-20-583
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the role of radiotherapy in pleural mesothelioma

Abstract: Malignant pleural mesothelioma is an uncommon thoracic cancer with a relatively poor outcome, which has only seen modest improvements when compared to non-small cell lung cancer. The mainstays of treatment have been surgery and systemic therapy, with radiation reserved for palliation or as an adjunct. However, there is re-emergent interest in the use of radiotherapy in the treatment of mesothelioma, given recent technical advances in radiotherapy delivery which permit increased treatment accuracy. This overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The highest quality evidence for palliative radiotherapy comes from the phase II SYSTEMS trial, which reported pain improvement in only 35% using 20 Gy in five fractions [ 59 ]. Since PM has a low α/β ratio, predicting better responses to dose-escalated hypofractionated regimes [ 60 ], the SYSTEMS trial was followed by the phase III RCT, SYSTEMS-2, which compared 36 Gy in six fractions to 20 Gy in five fractions [ 61 ]. Mature data from this trial are expected during 2024.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…The highest quality evidence for palliative radiotherapy comes from the phase II SYSTEMS trial, which reported pain improvement in only 35% using 20 Gy in five fractions [ 59 ]. Since PM has a low α/β ratio, predicting better responses to dose-escalated hypofractionated regimes [ 60 ], the SYSTEMS trial was followed by the phase III RCT, SYSTEMS-2, which compared 36 Gy in six fractions to 20 Gy in five fractions [ 61 ]. Mature data from this trial are expected during 2024.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Localised radiotherapy is used for multiple purposes in treating mesothelioma -ranging from treatment of procedure tract metastases, adjuvant hemi-thoracic radiation as part of aggressive multimodality therapy, and as palliative therapy to individual lesions 7 . However, high dose radiotherapy for local control can have toxicities, and does not palliate symptoms in a wholly effective manner [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, high-dose RT for local control can have toxic effects and does not palliate symptoms in a wholly effective manner. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%